New governance modes for Germany's financial reporting system - Jochen Zimmermann; Philipp Volmer; Jörg Werner (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
The question raised in this paper is whether changes over the last 20 years in the German financial accounting system signal a retreat of the nation state from this policy field. Using a comprehensive perspective on accountancy we consider the steps in the accounting process, i.e. standard setting, enforcement and disclosure, and analyse whether significant privatisation tendencies can be observed in accounting, whether and how the state safeguards its scope for interventions in the public interest and how these changes compare to the ongoing globalisation in accounting. We find that changes in all these areas are first of all driven by the application of European legislation, but also by voluntary harmonisation and an increased involvement of private actors. Altogether, a shift towards a (more) societal governance mode can be witnessed. However, the State increases its interventions at the same time by regulating arenas in which it was previously not active.
Keywords: 330; Bilanzrecht; Selbstverwaltung; Deutschland